PRE AND POST MERGER PERFORMANCE OF SBI - REDDY, J.MOUNIKA; KUMAR, G.VINEEEL (International Journal of Psychosocial Rehabilitation, 2020)
-Mergers are playing a crucial role in the growth of Indian banking sector. Mergers took place by considering various catalysts that leads to inorganic growth of the firm, increases capital base and expansion of business growth. The study at present mainly focuses on the merger that took place in one of the biggest banks of India i.e. SBI with its associate banks (which are running into losses).This research mainly focuses on the financial performance of the SBI bank before and after merger with special reference to key performance indicators (KPI) and focuses on the area of profitability, liquidity, efficiency and risk. The study also focuses on finding out the reasons on the performance of the banks after merging